Taujih Methodology and Its Relevance in Understanding Similar Editions in the Qur'an: (Metodologi Taujih dan Relevansinya dalam Memahami Redaksi Serupa Dalam Al-Qur’an) - Muslich Marzuki Mahdhor (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2026)
The Qur’an possesses distinctive linguistic characteristics, one of which is the phenomenon of similarly or identically worded verses (mutasyabih al-lafdzi). This phenomenon has generated diverse responses, ranging from Orientalist views that regard it as an indication of textual irregularity to Muslim scholars who understand it as part of the Qur’an’s rhetorical inimitability (i‘jaz Al-Qur’an).This study specifically aims to: 1) identify the forms of mutasyabih al-lafdzi in the Qur’an; 2) analyze the methodological principles of taujih in explaining variations among similar verses, and; 3) formulate a systematic framework of taujih principles integrated with classical tafsir and modern Qur’anic linguistics, while offering a scholarly critique of Orientalist views on Qur’anic repetition. This research employs a qualitative descriptive-analytical approach through a literature review of classical and contemporary tafsir works as well as specialized studies on taujih al-mutasyabih al-lafdzi. The analysis applies semantic, contextual, and rhetorical perspectives to uncover the relationship between lexical variation and the communicative purposes of the verses. The findings indicate that similarities in Qur’anic wording are not random but follow systematic and functional linguistic patterns. Each variation reflects meaningful adjustments to thematic context, pedagogical aims, and discourse structure. The novelty of this study lies in formulating a structured and integrative taujih framework that bridges classical exegetical tradition with modern linguistic theory and effectively addresses claims of textual inconsistency in the Qur’an. Thus, this study affirms the strategic role of taujih in strengthening the Qur’an’s internal coherence and deepening understanding of similarly worded verses.